Are Therapeutic Human Mesenchymal Stromal Cells Compatible with Human Blood?123. (18th June 2012) - Moll, Guido; Rasmusson‐Duprez, Ida; von Bahr, Lena; Connolly‐Andersen, Anne‐Marie; Elgue, Graciela; Funke, Lillemor; Hamad, Osama A.; Lönnies, Helena; Magnusson, Peetra U.; Sanchez, Javier; Teramura, Yuji; Nilsson‐Ekdahl, Kristina; et al.
Abstract: Multipotent mesenchymal stromal cells (MSCs) are tested in numerous clinical trials. Questions have been raised concerning fate and function of these therapeutic cells after systemic infusion. We therefore asked whether culture‐expanded human MSCs elicit an innate immune attack, termed instant blood‐mediated inflammatory reaction (IBMIR), which has previously been shown to compromise the survival and function of systemically infused islet cells and hepatocytes. We found that MSCs expressed hemostatic regulators similar to those produced by endothelial cells but displayed higher amounts of prothrombotic tissue/stromal factors on their surface, which triggered the IBMIR after blood exposure, as characterized by formation of blood activation markers. This process was dependent on the cell dose, the choice of MSC donor, and particularly the cell‐passage number. Short‐term expanded MSCs triggered only weak blood responses in vitro, whereas extended culture and coculture with activated lymphocytes increased their prothrombotic properties. After systemic infusion to patients, we found increased formation of blood activation markers, but no formation of hyperfibrinolysis marker D‐dimer or acute‐phase reactants with the currently applied dose of 1.0–3.0 × 10 6 cells per kilogram. Culture‐expanded MSCs trigger the IBMIR in vitro and in vivo. Induction of IBMIR is dose‐dependent and increases after prolonged ex vivo expansion. Currently applied doses of low‐passage clinical‐grade MSCs elicit only minor systemic effects, but higher cell doses and particularly higher passage cells should be handled with care. This deleterious reaction can compromise the survival, engraftment, and function of these therapeutic cells. Stem Cells 2012;30:1565–1574